2022
DOI: 10.1080/10717544.2022.2086939
|View full text |Cite
|
Sign up to set email alerts
|

Olmesartan medoxomil self-microemulsifying drug delivery system reverses apoptosis and improves cell adhesion in trinitrobenzene sulfonic acid-induced colitis in rats

Abstract: Olmesartan medoxomil (OM) is an angiotensin receptor blocker. This study aimed to investigate the effects of OM self-microemulsifying drug delivery system (OMS) in trinitrobenzene sulfonic acid (TNBS)-induced acute colitis in rats. Besides two control groups, five TNBS-colitic-treated groups ( n = 8) were given orally sulfasalazine (100 mg/kg/day), low and high doses of OM (3.0 and 10.0 mg/kg/day) (OML and OMH) and of OMS (OMSL and OMSH) for seven days. A colitis activity score was calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(18 citation statements)
references
References 62 publications
0
18
0
Order By: Relevance
“…All studies reported at least one of the following scoring systems to evaluate disease activity: DAI, MaS or histologic assessment. Seventeen out of 35 studies used DAI to evaluate the experimental model [14, 22, 23, 26–28, 30, 31, 38, 39, 42, 47–52], 17/35 studies used MaS [28, 30, 32, 34, 36, 37, 40, 41, 44–47, 50–54] and 34/35 studies used a histologic score [14, 22–26, 28–54]. Six out of the 35 studies used the three scoring systems [28, 30, 47, 50–52], 11/35 used MaS and histologic assessment [22, 32, 34, 36, 37, 40, 41, 44–46, 54] and 10/35 used DAI and histologic assessment [14, 22, 23, 26, 31, 38, 39, 42, 48, 49].…”
Section: Resultsmentioning
confidence: 99%
“…All studies reported at least one of the following scoring systems to evaluate disease activity: DAI, MaS or histologic assessment. Seventeen out of 35 studies used DAI to evaluate the experimental model [14, 22, 23, 26–28, 30, 31, 38, 39, 42, 47–52], 17/35 studies used MaS [28, 30, 32, 34, 36, 37, 40, 41, 44–47, 50–54] and 34/35 studies used a histologic score [14, 22–26, 28–54]. Six out of the 35 studies used the three scoring systems [28, 30, 47, 50–52], 11/35 used MaS and histologic assessment [22, 32, 34, 36, 37, 40, 41, 44–46, 54] and 10/35 used DAI and histologic assessment [14, 22, 23, 26, 31, 38, 39, 42, 48, 49].…”
Section: Resultsmentioning
confidence: 99%
“…Disease activity scores were significantly reduced due to OMS, indicating its potential in managing Crohn's disease colitis (Figure 8). [196] Thakkar and colleagues developed OLM nanosuspensions for improved solubility using the media milling approach. The nanosuspension delivery resulted in increased permeation rates, about double the amount diffused through the biological membrane.…”
Section: Benicar (Olmesartan Olm)mentioning
confidence: 99%
“…Western blot analysis of E-cadherin expression, Bcl-2 associated X protein (Bax), Bcl-2, and cleaved caspase-3. Reprinted from [196] under the terms of the Creative Commons Attribution License (http://creativecommons.org/licenses/by/ 4.0/). The nanosuspension and pure drug permeability coefficients were determined to be 0.72×10 À 8 cm 2 /s and 0.18×10 À 8 cm 2 /s, respectively.…”
Section: Benicar (Olmesartan Olm)mentioning
confidence: 99%
See 2 more Smart Citations